A xylanase from Streptomyces sp. FA1: heterologous expression, characterization, and its application in Chinese steamed bread. (1st May 2016) - Xu, Yang; Wu, Jing; Zheng, Kaixuan; Wu, Dan
Abstract: Xylanases (EC 3.2.1.8) are hydrolytic enzymes that have found widespread application in the food, feed, and paper-pulp industries. Streptomyces sp . FA1 xynA was expressed as a secreted protein in Pichia pastoris, and the xylanase was applied to the production of Chinese steamed bread for the first time. The optimal pH and the optimal temperature of XynA were 5.5 and 60 °C, respectively. Using beechwood as substrate, the K m and V max were 2.408 mg mL −1 and 299.3 µmol min −1 mg −1, respectively. Under optimal conditions, a 3.6-L bioreactor produced 1374 U mL −1 of XynA activity at a protein concentration of 6.3 g L −1 after 132 h of fermentation. Use of recombinant XynA led to a greater increase in the specific volume of the CSB than could be achieved using commercial xylanase under optimal conditions. This study provides the basis for the application of the enzyme in the baking industry.